Alkaloids from the stems of Clausena lansium and their neuroprotective activity. Issue 56 (14th July 2017) - Liu, Jie; Du, Yi-Qian; Li, Chuang-Jun; Li, Li; Chen, Fang-You; Yang, Jing-Zhi; Chen, Nai-Hong; Zhang, Dong-Ming
Abstract : Eight new alkaloid derivatives (1–5 ), including three pairs of enantiomers, were obtained from Clausena lansium, and showed moderate neuroprotective effects. Abstract : Eight new alkaloids, including three pairs of enantiomers (+)-(2′ S, 3′ R )-clauselansine A (1a ) and (−)-(2′ R, 3′ S )-clauselansine A (1b ); (+)-(2′ S, 3′ R )-clauselansine B (2a ) and (−)-(2′ R, 3′ S )-clauselansine B (2b ); (+)-(3 S, 4 R, 5 S, 6 S )-clauselansine C (3a ) and (−)-(3 R, 4 S, 5 R, 6 R )-clauselansine C (3b ), (+)-(1′ R, 2′ R, 6′ R )-claulansine B (4a ), and (+)-(1′ R, 2′ R )-claulansine D (5a ), together with twelve known alkaloids (4b, 5b, 6a, 6b, 7a, 7b and8–13 ) were isolated from the stems of Clausena lansium . Their structural elucidation and stereochemistry determination were achieved by spectroscopic and chemical methods including 1D and 2D NMR experiments, especially the employment of electronic circular dichroism calculation spectra, Mosher's method, and Snatzke's method expressed by the induced circular dichroism spectrum. Compounds1b, 2a, 3b, 5a, and5b inhibited PC12 cell damage induced by Okadaic Acid, and increased cell viability from 70.5 ± 5.4% to 83.4 ± 4.1%, 91.2 ± 10.1%, 83.5 ± 7.8%, 89.7 ± 4.8%, 83.3 ± 5.9% at 10 μM, respectively.